Socialization and Internalization of Qurâanic Verse by Enjoy Learning Arabic - Akmaliyah, Akmaliyah (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: Arabic is a language of the Arabs and Muslims used for religious as well as mundane purposes. As one of the international languages spoken by many people, Arabic is also the language of science. Like any other languages in the world, Arabic has its characteristics. Among them is its ability to create and produce the sounds representing numbers and letters, in which a variety of meanings is so rich yet distinguishable. This study tries to elaborate on how the process of socialization and internalization of Al-Qurâanic verse by enjoy learning Arabic. By using the qualitative method, this study showed that mastery of Arabic can be done through fun learning of the language. Materials presented through this process of learning can support the efforts of both socialization and internalization of Al-Quran, because they are associated in such a way with the verses of Al-Quran. Learning the Arabic language, in any type and level of education, should be done with a variety of learning strategies and fun. Psychologically, this situation impacts good study output or a positive learning transfer to the learners, in order he/she may be able to read and understand Al-Quran. A fun learning process is expected to be a stimulus for âsyiarâ or dissemination of the values of Al-Quran and Arabic language as its vehicle. KEY WORDS: Enjoy Learning; Arabic Language, Al-Qurâanic Verses; Learning Process; Socialization and Internalization.About the Author: Akmaliyah is a Senior Lecturer at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. E-mail address is: akmaliyah@gmail.comHow to cite this article? Akmaliyah. (2016). âSocialization and Internalization of Qurâanic Verse by Enjoy Learning Arabicâ in TAWARIKH: International Journal for Historical Studies, Vol.8(1) October, pp.79-92. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (May 24, 2016); Revised (July 30, 2016); and Published (October 28, 2016).